2009
DOI: 10.1074/jbc.m109.033076
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor CcpN from Bacillus subtilis Uses Different Repression Mechanisms at Different Promoters

Abstract: CcpN, a transcriptional repressor from Bacillus subtilis that is responsible for the carbon catabolite repression of three genes, has been characterized in detail in the past 4 years. However, nothing is known about the actual repression mechanism as yet. Here, we present a detailed study on how CcpN exerts its repression effect at its three known target promoters of the genes sr1, pckA, and gapB. Using gel shift assays under nonrepressive and repressive conditions, we showed that CcpN and RNA polymerase can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…The 205-nt sRNA is expressed under gluconeogenic and repressed under glycolytic conditions mainly by CcpN but also to a minor extent by CcpA, both regulators are involved in carbon catabolite repression (Figure 4) (22, 6264). …”
Section: Base-pairing Srnas That Encode Characterized Small Proteinsmentioning
confidence: 99%
“…The 205-nt sRNA is expressed under gluconeogenic and repressed under glycolytic conditions mainly by CcpN but also to a minor extent by CcpA, both regulators are involved in carbon catabolite repression (Figure 4) (22, 6264). …”
Section: Base-pairing Srnas That Encode Characterized Small Proteinsmentioning
confidence: 99%
“…The repression mechanism of CcpN has been elucidated using various techniques [91]. EMSAs demonstrated that CcpN and RNA polymerase can bind simultaneously to the sr1, pckA or gapB promoter and that CcpN cannot impede closed complex formation at these promoters.…”
Section: Ccpn -Latest Member Of the Ccpa-independent Catabolite Reprementioning
confidence: 99%
“…CcpN binds upstream of and overlapping the sr1 promoter, 33 whereas CcpA binds 250 upstream of the transcription start site (TSS) at a cre site. CcpN represses sr1 transcription in the presence of ATP and slightly acidic pH (6.5) 34 by interacting with the α-subunit of the RNA polymerase, thereby inhibiting promoter escape 35 . Transcriptomics and northern blotting suggested a second target for SR1, the gapA operon.…”
Section: Srnas From Bacillus Subtilismentioning
confidence: 99%